Comparison of Vitamin, Anthocyanin, and Bioactive Compounds from Gajah and Padi Jengkol (Archidendron jiringa) Peel as Potential Natural Antioxidants. Issue 1 (March 2020) - Hidayah, N; Lubis, R; Nurhaita,
Abstract: Synthetic antioxidants have recently been reported to be dangerous for animal and human health. Thus, natural antioxidants from by-product plant materials are potential to replace synthetic ones. Vitamin C, E, carotenoid, anthocyanin, and phenolic compound have been proposed as a biological antioxidants. This experiment was designed to evaluate and compare the content of vitamin (C and E), anthocyanin, and bioactive compound (tannin and total phenol) from Gajah and Padi jengkol peel to assess their potentials as natural antioxidants. Data were analyzed descriptively by calculated the average of the data. The results showed that there were no differences between vitamin C and E percentage from gajah and padi Jengkol peel. Percentage of vitamin C was in low category and vitamin E was in medium category. Anthocyanin content of Padi Jengkol peel was 37.35% higher than Gajah Jengkol peel. Likewise, tannin and total phenol content of padi jengkol peel were almost 2 times higher than the gajah jengkol peel. It is concluded that padi jengkol peel are more potential to be used as a natural antioxidants than gajah jengkol peel.